Métodolia paracontrole de recalques em estruturas de concreto armado por meio de nivelamento geométrico de precisão - Corrêa, Cícero Pimentel (2012)
Civil construction on the rise over the past years, and the events of structural accidents in the meantime, gave rise to a methodology for monitoring structure settlings through precise geometric leveling topographic surveys. The methodology was conducted in a reinforced concrete drinking water reservoir structure, of the Rio Grande do Sul Basic Sanitation Company (CORSAN), now at its final construction stage, located in the municipality of Santa Cruz do Sul RS. All data obtained from the newly developed methodology were observed right after the conclusion of the work and during the beginning of its utilization. We utilized a set comprising an optical mechanic geodesic level and metallic millimeter ruler for carrying out settling control, and the readings on the metallic rulers were analyzed. Evolution charts of the settlings were made in order to check the behavior of the speeds and their acceleration rate.